The Design and Implementation of a Virtual Reality Program for Improving Situated Consecutive Interpreting Skills - Chou, Isabelle; Zhang, Cheng; Yu, Yuemeng (Learning Technologies and Systems, 2021)
In this paper, we present the Platform of Immersion Interpreting Learning in Virtual Reality and AI Assessment, embedded with three classical virtual scenarios in consecutive interpreting, aiming at improving situated consecutive interpreting skills for student interpreters at both undergraduate and postgraduate levels. This proposed project also integrates the AI assessment system into the virtual environment. It can evaluate students’ performance based on their reaction time, level of completeness, accuracy, and fluency of the interpreting task. The project supports both visual and auditory channels of interaction, with learner’s interpreted speech as the input and outputs include graphical scenes and speech from the speaker in the scenario. Moreover, the project allows interpreting trainers to design their training drills based on their teaching plans. Throughout a pre-and post-test of 10 graduate students, it is found that their average reaction time was shorter in post-test, and the level of interpreting fluency and accuracy were also improved after the training.